ANALISIS IMPLEMENTASI KEBIJAKAN ZONASI DALAM PEMERATAAN PENDIDIKAN - Risna Risna; Lisdahlia Lisdahlia; Syamsul Edi (Institusi Agama Islam Negeri (IAIN) Bone, 2020)
Equitable education is very important in the delivery of education in this country. One of the government's efforts to accelerate the distribution of education is the establishment of the zoning system contained in Permendikbud No. 14 of 2018, namely the Acceptance of New Students (PPDB) which emphasizes the distance or radius between student homes and schools, so who is closer to the school he is more entitled to get educational services from the school. This research was conducted with the aim of describing and analyzing the implementation of zoning policies in the distribution of education. This research uses a qualitative research method with descriptive research type. Data collection techniques using observation, interviews and documentation. Data analysis techniques using data reduction, data presentation and conclusion drawing. The results showed that the implementation of the school zoning system was not yet fully implemented. It is seen that more negative impacts are felt by those involved in implementing this policy than positive impacts.